Business Legal Assistance And Improvement Of Product Packaging ‘Bangreng Crackers Wagir Bu Wati’ In The Framework Of Msme Digital Transformation - Asri Widyasanti; Ariq Helmi Naufal; Nadiya Sulistiyani; Renata Marintan Olivia; Selaraswati Fajrin (Universitas Serang Raya, 2022)
Business legal assistance and packaging improvement activities are part of the entrepreneurship thematic Community Service (PPM) activity which was carried out in a hybrid way in Wado Village, Wado District, Sumedang Regency. The organizers of the activity consisted of 4 students and 1 supervisor. The PPM locations are chosen to meet the needs of entrepreneurship growth in the Sumedang area, which are based on a variety of natural and human resources. The development activities of Micro, Small and Medium Enterprises (SMEs) are aimed at increasing the economic development of SMEs in Wado Village and as a means of developing and reintroducing Bangreng cracker MSME products which are the hallmark of Sumedang, especially in Wado Village. The method of implementing PPM activities uses a participatory approach and data collection is carried out through observation and interviews for 1 month. The activity also involves collaboration between universities, Bappeda Sumedang, the Cooperative Service and the SMES Service. The findings of the initial identification revealed that SMEs continue to have difficulty understanding bussiness permissions such as Bussiness Permit Number (NIB) and Home Industry Food Production Certificate (SP-PIRT). SME Crackers Bangreng Wagir bu Wati has received Food Safety Counseling training, has an NIB permit, SP-PIRT, and good packaging to be ready to go digital as a result of the socializing and assistance efforts for business licensing. Generally, the assistance and development of SME products is very useful for the progress of SMEs in welcoming the digital transformation of SMEs in Sumedang Regency.